Analisis Profitabilitas Untuk Mengukur Kinerja Keuangan Pada PT. Adhi karya (Persero) Tbk - Nurlela, Nurlela; Surbakti, Eka Wulandari; Ananda , Shela (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2024)
The purpose of this study was to determine the financial performance and profitability of PT Adhi Karya (perseo) Tbk during the period 2020-2023. The data analysis technique used is quantitative with a descriptive approach and only focuses on numbers. The data collection method used in this research is literature study, the type of research data is secondary data in the form of financial statements of PT Adhi Karya (perseo) Tbk published at www.idx.co.id. Based on the results of the study, it shows that the company's financial performance as measured by Return On Assets in 2020 - 2023 is below the industry average with a poor category. In 2020-2021, financial performance is measured by Return On Equity which is below the industry average with a poor category, while in 2022-2023 financial performance seen from ROE is above the industry average with a good category. In 2020-2023, financial performance as measured by Net Profit Margin was below the industry average with a less good category